(3GdGNJjGQGJs - (3eMeO Hf GadGWhf GdHQhShj, CadGWhf RGOg, GHf GadGWhf , J (B937 (3g` s
(3ChdgG (B:s
(3jHOC HGdeSGFd GdeJYdbI HGdWgGQI s
(3BNQgG (B:s
(3hMdjJgG PgH Ydi CQHYI ChLg CjVkG Ydi eG HjfG ai GdaVI ef TQM GdWMGhi Je s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B65s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B48s
Keywords: (3Gdabg GdMfajs